Epigenetic Differences Arise in Endothelial Cells Responding to Cobalt–Chromium - da C. Fernandes, Célio Junior [UNESP]; da Silva, Rodrigo A. Foganholi; de Almeida, Gerson Santos [UNESP]; Ferreira, Marcel Rodrigues [UNESP]; de Morais, Paula Bertin [UNESP]; Bezerra, Fábio [UNESP]; Zambuzzi, Willian F. [UNESP] (MDPI, 2023)
Cobalt–chromium (Co-Cr)-based alloys are emerging with important characteristics for use in dentistry, but the knowledge of epigenetic mechanisms in endothelial cells has barely been achieved. In order to address this issue, we have prepared a previously Co-Cr-enriched medium to further treat endothelial cells (HUVEC) for up to 72 h. Our data show there is important involvement with epigenetic machinery. Based on the data, it is believed that methylation balance in response to Co-Cr is finely modulated by DNMTs (DNA methyltransferases) and TETs (Tet methylcytosine dioxygenases), especially DNMT3B and both TET1 and TET2. Additionally, histone compaction HDAC6 (histone deacetylase 6) seems to develop a significant effect in endothelial cells. The requirement of SIRT1 seems to have a crucial role in this scenario. SIRT1 is associated with a capacity to modulate the expression of HIF-1α in response to hypoxia microenvironments, thus presenting a protective effect. As mentioned previously, cobalt is able to prevent HIF1A degradation and maintain hypoxia-related signaling in eukaryotic cells. Together, our results show, for the first time, a descriptive study reporting the relevance of epigenetic machinery in endothelial cells responding to cobalt–chromium, and it opens new perspectives to better understand their repercussions as prerequisites for driving cell adhesion, cell cycle progression, and angiogenesis surrounding this Co-Cr-based implantable device.
Keywords: angiogenesis; biomaterial; cobalt–chromium; DNA methylation; endothelial cells; epigenetics; histone acetylation